IMAGINE DAN PLOTTING : VISUALISASI CYBERLOVE DAN CYBERSEX PASANGAN ROLEPLAYER K-POP DI MEDIA SOSIAL X - Nuzul Novianti; Iwan Koswara; Meria Octavianti (Jurnal Netnografi Komunikasi, 2025)
This paper delves into the phenomenon of imagine and plotting among K-Pop roleplayer couples on the social media platform X, interpreting these practices as a form of visualizing cyberlove and cybersex. Through a descriptive qualitative approach grounded in the phenomenological method, this research shows how these activities emerge and unfold as key elements of interaction within the roleplaying community. Imagine and plotting are examined as virtual expressions that replace physical body language, offering couples an avenue to communicate intimacy and emotional depth. These practices highlight the creativity and flexibility inherent in the virtual domain, where participants construct immersive and dynamic scenarios tailored to their preferences and consent. This paper also uncovers the diverse relationship dynamics within this space, noting how roleplayer couples navigate dominance, responsiveness, and emotional reciprocity in their interactions. Furthermore, imagine and plotting are shown to possess the potential to transcend the digital realm, enabling relationships formed virtually to evolve into meaningful real-life connections. This paper positions these practices as not merely recreational but as profound mediums of self-expression and relational development, reflecting the interplay between virtual creativity and emotional authenticity in shaping modern romantic experiences.